2001
DOI: 10.1093/brain/124.12.2372
|View full text |Cite
|
Sign up to set email alerts
|

Interictal cardiac autonomic dysfunction in temporal lobe epilepsy demonstrated by [123I]metaiodobenzylguanidine-SPECT

Abstract: We studied the post-ganglionic cardiac sympathetic innervation in patients with chronic temporal lobe epilepsy (TLE) by means of [(123)I]metaiodobenzylguanidine-single photon computed tomography (MIBG-SPECT) and evaluated the effects of carbamazepine on cardiac sympathetic innervation. TLE is frequently associated with dysfunction of the autonomic nervous system. Autonomic dysregulation might contribute to unexplained sudden death in epilepsy. Anticonvulsive medication, particularly with carbamazepine, might a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 40 publications
4
70
2
5
Order By: Relevance
“…However, the cardiac signs found in our series such as: asystole and bradycardia may also be suggestive of cardiac dysfunction secondary to left insula as has previously been reported in patients with temporal lobe epilepsy [195][196][197][198] and confirmed in 2009 by Koseoglu et al [199] The epileptic activity spreads through the limbic system with the involvement of the amygdala, hypothalamus, and thalamus. These, in turn stimulate the autonomic system at medullar level including the nucleus tractus solitarius and the nucleus ambiguous which generate sympathetic and parasympathetic discharges.…”
Section: Insula Lobe Neurocysticercosissupporting
confidence: 82%
“…However, the cardiac signs found in our series such as: asystole and bradycardia may also be suggestive of cardiac dysfunction secondary to left insula as has previously been reported in patients with temporal lobe epilepsy [195][196][197][198] and confirmed in 2009 by Koseoglu et al [199] The epileptic activity spreads through the limbic system with the involvement of the amygdala, hypothalamus, and thalamus. These, in turn stimulate the autonomic system at medullar level including the nucleus tractus solitarius and the nucleus ambiguous which generate sympathetic and parasympathetic discharges.…”
Section: Insula Lobe Neurocysticercosissupporting
confidence: 82%
“…In a similar manner, other authors reported how ventricular asystole can occur because of vagal activation in the operating room (18). Recently, altered postganglionic cardiac sympathetic innervation with a predominant parasympathetic cardiac activity was demonstrated in patients with TLE by using MIBG-SPECT and domain analysis of heart-rate variability (19,20). Nevertheless, the question whether the underlying mechanism of ictal cardiac arrest is a direct vagally mediated activation of the cardiac conduction system occurring during the seizure, or an uncoordinated autonomic releasing effect (21), remains to be resolved.…”
Section: Discussionmentioning
confidence: 70%
“…The emergence of ictal activity in these structures or spread to these structures can lead to sympathetic and parasympathetic changes that affect the heart rate in patients with epilepsy (7). It was shown that metaiodobenzylguanidine (MIBG) uptake is reduced at myocardial sympathetic nerve terminals in patients with chronic TLE and this reduction has been suggested to be an indicator for reduced post-ganglionic sympathetic innervation (21). Decreased innervation may lead to hypersensitivity of cardiac beta-adrenergic receptors.…”
Section: Peri-ictal Cardiac Changesmentioning
confidence: 99%